The Effectiveness of Virtual Classroom in TOEFL Preparation - Nyayu Yayu Suryani (Acitya: Journal of Teaching and Education, 2021)
Communication technology has grown dramatically in Indonesia. Virtual classroom is an integration of information technology through the use of the internet to connect teachers and students. The aim of this research is to find out the effectiveness the using virtual classroom in TOEFL preparation and to improve students’ score in TOEFL preparation. The population in this research was all of students Nursing Science Study Program Institute of Health Science and Technology of Muhammadiyah Palembang. In order to select the sample, the purposive sampling technique will be implemented, the sample of this research was the seventh semester students of Institute of Health Science and Technology Muhammadiyah Palembang. Nursing science Study program in Academic Year 2020/2021.The data collection of this research is carry out online through Zoom meeting. To verify the hypotheses, the data used paired sample t-test and independent sample t-test was 0.008 which was lower than 0.05.The findings show the positive effects using virtual classroom in TOEFL preparation. Keywords: TOEFL preparation;technology;virtual classroom